Improving Healthcare Services by Quality Function Deployment (QFD) - Al Memari, Ahmed Salem (2016)
The tools of the Total Quality Management (TQM) have gained high importance due to increasing competitions in the healthcare industry. As a selling approach needs to be based on management assurance, this has to be applied hospital-wide with a systematic approach for the continuous quality improvement. The observations from the selected hospital for this research showed that it is struggling to meet customers' expectations in some areas. The quality function deployment (QFD) is a systematic technique for designing services or products that are based on the customers' needs. Therefore, the tool is widely used in almost all industries. This research paper elaborates on the reasons the quality function deployment (QFD) is selected as a technique to develop a total quality healthcare model. With the help of a hospital-based case study, this research paper discovers the possibility of using the quality function deployment (QFD) in the healthcare service. The paper showed some limitations of the conventional quality function deployment (QFD) outside the physical industrial production and presented modifications as an extension of the quality function deployment (QFD) in the healthcare service. Based on the outcomes, a total quality model was developed to guide the healthcare management in their total quality development.